1996
DOI: 10.1097/00005373-199608000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus and the Trauma Patient

Abstract: Despite the profound immunosuppression in this group of patients, the incidence of bacterial infectious complications was independent of the CD4+ count (p = 0.958), but was associated with increases in the ISS (p = 0.003).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A study by Guth et al reported similar results. 10 The CD8 level of the trauma group is different than the CD8 level in the other three surgery-based diseases. In trauma patients, the CD8 level of the sepsis group was higher than the level of the non-sepsis group.…”
Section: Resultsmentioning
confidence: 86%
“…A study by Guth et al reported similar results. 10 The CD8 level of the trauma group is different than the CD8 level in the other three surgery-based diseases. In trauma patients, the CD8 level of the sepsis group was higher than the level of the non-sepsis group.…”
Section: Resultsmentioning
confidence: 86%
“…HIV patients have a moderately increased risk of complications, including wound infection (Paiement et al 1994), especially after open fractures. However, it seems that the degree of contamination of the wound in open injuries (Guth et al 1996, Harrison et al 2002) and the lifestyle of the patients (Habermann et al 2008) have more influence on outcome than HIV infection alone. There is increasing evidence both from high-income countries and from LMICs that the end outcomes after surgery in general are no worse for patients with HIV than for other patients (Cacala et al 2006, Duane et al 2008, Stock et al 2010, Patel et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One potential risk factor for SSI is HIV infection. HIV-positive patients may be more susceptible to SSI due to immune dysfunction and other comorbidities associated with HIV [8][9][10][11][12][13][14][15]. However, research on the incidence of Neurosurgical Site Infection (NSSI) in HIV-positive patients is limited and the results have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%